Придон: [роман] / Юрий Никитин - Никитин Юрий Александрович (Эксмо, 2003)
Цикл: Троецарствие Экземпляры: ЦБ (20210511) / Инвентарный номер: 53722 / Цена: 150.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Н 62 / ГРНТИ: 17.82.30 / ББК: 84(2Рос=Рус)6-44